# Express recurrence in closed form

I am having trouble understanding the process of expressing the following recurrence in its' closed form.

First of all, I do not really understand what "closed form" means. If someone could elaborate a little bit on this, it would be much appreciated.

Second, Could you explain the nature of the function itself, as in, what it is explicitly trying to do?

Here is the recurrence function:

$$F_{0} = 7$$

$$F_{N} = 5F_{N-1} + 3, \ \ ( N > 0 ).$$

Express $F_{N}$ in closed form

The final answer, should be the following:

$$\frac{31\cdot(5^N) - 3}{ 4}$$

Thank you so much for your help and additional explanations you may throw in. I am very lost in regards to what to do.

J.

## UPDATE

Some of the process is here:

• "Closed form" is an analytical expression for the generic term of your sequence, that allows you to compute it without knowing the previous terms. In this case, $F(n)=31\cdot 5^n - 3/4$ is a closed form. – Giuseppe Negro Dec 9 '14 at 9:21
• I would first take an ansatz $F_{N} = \lambda^{N}$ and then solve the homogeneous and particular parts separately. – Mattos Dec 9 '14 at 9:26
• @GiuseppeNegro Do you know the process of how to get there? – J Tarantino Dec 9 '14 at 9:30
• @Mattos: I’m unsure why did you change parentheses to subscript, but since original poster did not object, I rest it in place. – Incnis Mrsi Dec 9 '14 at 9:32
• @Incnis Mrsi: Because sequences are usually defined by a subscript and also, the OP didn't use latex script at all so it was an educated guess as to what he was trying to ask. Now it looks even worse because we have $F_{N} = 5F(N-1)$. You'll need to edit it again now to have it as either $F_{N} = 5F_{N-1}$ or $F(N) = 5F(N-1)$ to avoid confusion. – Mattos Dec 9 '14 at 9:40

HINT

You have already the "final" exprssion :

$f(n) = (31 \times 5^n -3)/4$.

What you have to do is to prove - by induction - that it holds, i.e. that it satisfies the recurrence relation for $f(n)$.

(i) base case : $n=0$

For $n=0$ the recursive definition of $f(n)$ has : $f(0)=7$.

We have to check that it matches with the closed expression :

$$f(0) = (31 \times 5^0 -3)/4 = (31 -3)/4 = 28/4 = 7.$$

It's Ok.

(ii) induction step : assume that it holds for $n$ and show that it holds for $n+1$.

For the closed form, we can try with :

$f(n) = ac^n+b$.

For $n=0$ we have : $f(0)=7=a+b$; thus :

$a = 7-b$.

Using the recurrence relation : $f(n+1)=5f(n)+3$ we have : $ac^{n+1}+b=5(ac^n+b)+3$.

With $c=5$ we can compute $b = - \frac {3}{4}$ and so : $a = 7-b = 7 + \frac {3}{4} = \frac {31}{4}$.

• do you know whats the process of getting there though? that is what I'm most interested in... I'll put some of the work in an update – J Tarantino Dec 9 '14 at 9:36
• @JTarantino - you can see here – Mauro ALLEGRANZA Dec 9 '14 at 9:40
• I've updated mia risposta... puoi vederla? grazie mile! – J Tarantino Dec 9 '14 at 9:46